Serum total prostate-specific antigen (tPSA): correlation with diagnosis and grading of prostate cancer in core needle biopsy - Nina Čamdžić; Suada Kuskunović-Vlahovljak; Mirsad Dorić; Svjetlana Radović; Edina Lazović Salčin; Mirsad Babić (Medicinski glasnik, 2020)
Aim: To investigate the impact of pre-treatment serum total prostate-specific antigen (PSA) level on prevalence of prostate carcinoma detection in prostate core needle biopsy, and its correlation with established prognostic factors. Methods: Prostate needle biopsy samples of 115 patients with available pre-treatment serum total PSA (tPSA) level were analysed. For all cases where morphology alone was insufficient, immunohistochemistry was performed using p63, CKHMW and AMACR antibody panel in order to confirm or exclude the existence of prostate carcinoma. Results: Statistically significant positive correlation between serum total PSA values and prevalence of finding prostate carcinoma in needle biopsy specimens was found (p=0.011), as well as in the case when the patients were classified into groups according to tPSA levels (p=0.028). Serum total PSA values and levels (level groups) showed significant positive correlation with Gleason score (p=0.029 and p=0.036, respectively) and Grade Group of prostate carcinomas (p=0.044 and p=0.046, respectively). Sensitivity of the screening test by using 4 ng/mL as cut off value for tPSA was 94.12% (CI: 80.32-99.28%), specificity 8.64% (CI: 3.55-17.00%), positive predictive value 30.19% (CI: 21.65-39.87%) and negative predictive value 77.78% (CI: 39.99-97.19%). Conclusion: The increase of serum tPSA value increases the likelihood of finding prostate cancer on needle biopsy specimens. Due to such findings and its positive correlation with a grade of prostate cancer, our study indicates that tPSA can still be considered as a useful tool both in detecting and predicting aggressiveness of prostate cancer.
Keywords: grade group; Gleason score; screening